2019
DOI: 10.1186/s12887-019-1407-9
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-recovery from severe acute malnutrition in children 6–59 months of age enrolled in the outpatient treatment program in Shebedino, Southern Ethiopia: a prospective cohort study

Abstract: BackgroundIn Ethiopia uncomplicated severe acute malnutrition (SAM) is managed at health posts level through the outpatient therapeutic program (OTP). Yet, evidence on the treatment success rate of the program is scarce. This study determines the treatment outcomes and predictors of time-to-recovery among children 6–59 months of age with SAM managed at the health posts level in Shebedino district, Southern Ethiopia.MethodsThis was a prospective cohort study that enrolled 216 children with SAM identified throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 17 publications
19
52
2
Order By: Relevance
“…At admission, 64.4% of participants showed up with other co-morbidities on top of SAM. Majority of children (64.9%) were hospitalized with marasmus (non-edematous) type of SAM, similar with some recent studies in Ethiopia [1,13,[25][26][27][28][29][30][31] but in contrary to that of Jimma [32], Hadiya, Ethiopia [33] and Uganda [34], which reported edematous type of SAM was highly encountered. This variation might be attributable to the multi-faceted causes of SAM all over the world.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At admission, 64.4% of participants showed up with other co-morbidities on top of SAM. Majority of children (64.9%) were hospitalized with marasmus (non-edematous) type of SAM, similar with some recent studies in Ethiopia [1,13,[25][26][27][28][29][30][31] but in contrary to that of Jimma [32], Hadiya, Ethiopia [33] and Uganda [34], which reported edematous type of SAM was highly encountered. This variation might be attributable to the multi-faceted causes of SAM all over the world.…”
Section: Discussionsupporting
confidence: 86%
“…This is similar with the findings from institution based researches in Bahirdar [13,35] that reported 16 days of recovery time. But this finding is far less than the report from Sidama zone Shebedino district of southern Ethiopia [29] which found the median LOS of 36 days. It is also lower than several studies conducted in the Ethiopia [1,8,11,24,32] and that of Yemen [36].…”
Section: Discussioncontrasting
confidence: 69%
“…This significant nonrecovery rate could be attributed by high burden of comorbidities, inappropriate feeding process of the RUTFs, non-adherence to follows due to long distance to access RUTFs and drugs in some OTP centers of the country (7,(33)(34)(35). Similarly, food insecurity could contribute to sharing food among family members and this may affect recovery rate of children (33). (60).…”
Section: Discussionmentioning
confidence: 99%
“…In the current review, eight studies (21,(24)(25)(26)(31)(32)(33)(34) revealed the independent predictors of recovery rate using hazard ratios. The predictors which were reported by the original studies were diarrhea (21,25,31,33), age>24 months (26,32,33) However, diarrhea, no edema and Amoxicillin were found to be independent predictors of recovery rate (Figure 8). The recovery rate of SAM children with diarrhea 16% less likely compared with those children with no diarrhea (HR=0.8, 95% CI: 0.75, 0.94).…”
Section: Predictors Of Recovery Rate Of Sam Children In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation